Acceptability of the FreeStyle Libre Flash Glucose Monitoring System: The Experience of Young Patients With Type 1 Diabetes. (March 2020) - Al Hayek, Ayman A; Robert, Asirvatham A; Al Dawish, Mohamed A
Background: In the current era of modern technology, the development of smart devices such as the flash glucose monitoring (FGM) systems helps patients with diabetes to effortlessly monitor their glucose levels more frequently. In this study, we determine the user acceptability of FGM among young patients with type 1 diabetes (T1D). Methods: A cross-sectional study was performed among 67 young patients with T1D in the age group of 13 to 19 years and who were managed on the FGM method for self-testing the glucose levels for a minimum of 6 months. The participants acceptability measures that were collected with a standard questionnaire and where they rated their experience with the system on a scale of 1 (strongly agree/painless) to 5 (strongly disagree/severe pain). In addition to the demographic and clinical parameters, a closed/structured questionnaire was administered, in order to record the prior and present skin issues, over a 6-month period. Results: From the patient statements regarding sensor application, 95.5% of the study population strongly agreed that the sensor application caused less pain than the routine finger-stick. Similarly, 85% of the users strongly agreed that using the sensor was comfortable, while 94% strongly agreed that they found the small size of the FGM made it easy to wear, 47.8% strongly agreed that wearing the sensor did not attract attention, 70.1% reported no discomfort under the skin, 80.6% stated that the sensor could be scanned without anyone noticing it, 89.6% felt that the sensor did not affect their daily activities, 91% strongly agreed that the sensor was very compatible with their lifestyle, 79.1% reported ease with taking a glucose reading with the scan, 89.6% reported that taking glucose readings with this system would not disrupt their daily activities, and 76.1% participants were excited to share with other individuals their experiences with this system. A comparison of the self-monitoring of blood glucose and freestyle techniques demonstrated that 83.6% participants strongly agreed that it was less painful to get glucose readings from the freestyle sensor, and that it was a more discreet (83.6%), more comfortable (85.1%), easier (95.5%), faster (82.1%), simpler (79.1%), more private (88.1%), and less stressful (77.6%) method, with minimal hassle (74.6%). It is notable here that 86.6% of the participants reported absolutely no pain when the freestyle sensor was applied; also, the majority of the participants (91%) reported no pain symptoms when scanning the sensor. Conclusion: The findings of this study clearly showed that the study population had a high level of acceptability of the FGM.